Angioleiomyoma uterus in an adolescent girl: a highly unusual presentation. - Sharma, C; Sharma, M; Chander, B; Soni, A; Soni, P (2014)
BACKGROUND: Uterine angioleiomyoma is a very rare gynecologic tumor; only a few such cases have been reported to date and we have found no such tumor reported in an adolescent girl. CASE: We report the case of a uterine angioleiomyoma in an adolescent girl. It presented as a huge abdomino-pelvic mass. The girl had severe menorrhagia and severe anemia. Intra-operatively no distinct planes were found between myoma and myometrium. Due to severe hemorrhage, she underwent sub-total abdominal hysterectomy. SUMMARY AND CONCLUSION: Uterine angioleiomyoma is an extremely rare tumor since only 16 such cases have been reported to date. Its appearance in an adolescent girl seems to be the first case of its kind. So it is being reported not only to familiarize the managing physicians with the possibility of such a tumor and its variable presentation, but also to highlight the need for inclusion of this tumor in WHO classification of tumors of the female genital tract.